M‑communication in Product Information Exchange – an International Comparison - Bartosik-Purgat, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The main objective of the paper is to identify the degree to which Social Networking Sites (SNSs) are used in communication related to gathering information about products via mobile devices (mobile communication). The research problem is presented in the context of Computer Mediated Communication theory (CMC). In the realisation of the main purpose of this paper, an attempt has been made to answer two research questions: firstly, is there a relationship between types of products and the frequency of gathering and conveying information about them via SNSs? Secondly, what role do mobile devices play in this communication? A comprehensive literature study has been complemented with an empirical research, conducted in four countries – China, Poland, the United States and Turkey. Two research methods: PAPI (Paper and Pen Personal Interview) and CAWI (Computer Assisted Web Interview) were used in the empirical research. The research showed a significant use of mobile devices (i.e. smartphones and tablets) in communication (gathering and conveying information about products) via SNSs, especially in relation to products such as electronic devices as well as clothes and footwear.